Analysis the Relationship between Direct Investment and Labor - Raden Parianom; Risna Triandhari; Freesca Syafitri; Mira Rahmi (Green Publisher Indonesia, 2023)
The establishment of the ASEAN Economic Community (AEC) makes the movement of labor in the ASEAN region more free and dynamic. This provides wider opportunities for Indonesian workers to get better jobs. On the other hand, the same opportunity is also owned by citizens of other ASEAN countries to enter the labor market in Indonesia. Based on several previous empirical studies, the entry of foreign workers into a country can significantly impact economic growth, both positively and negatively. The impact is greatly influenced by the skill level of a worker. High skilled labor tends to have a positive impact on economic growth. The increase in the number of foreign workers is also influenced by FDI and GDP. The amount of FDI received by a country tends to be positively correlated with the number of foreign workers. This is because the FDI provided has applied high technology so that the knowledge transfer process is needed by foreign experts. The tendency of foreign skilled workers who have higher wages than domestic workers makes wage inequality between workers. Increased employment of foreign workers could also widen the wage gap in Indonesia.